Trace Metal Lead Exposure in Typical Lip Cosmetics From Electronic Commercial Platform: Investigation, Health Risk Assessment and Blood Lead Level Analysis - Li, Yanan; Fang, Yanyan; Liu, Zehua; Zhang, Yahan; Liu, Kangli; Jiang, Luping; Yang, Boyuan; Yang, Yongdie; Song, Yongwei; Liu, Chaoyang (Frontiers in Public Health, 2021)
Lead (Pb) in lipstick products has become an increasing concern, which can cause safety problems to human body directly with diet. To investigate the Pb exposure and potential health risk level of typical popular lip cosmetics in Chinese e-commerce market, Python crawler was introduced to identify and select 34 typical popular lip cosmetics, including 12 lipsticks, 13 lip glosses, and 9 lip balms. And then this study used ICP-MS to determine the content of Pb. Furthermore, the ingestion health risk assessment method issued by United States Environmental Protection Agency (USEPA) and Monte Carlo simulation algorithm were applied to assess the probabilistic health risks of adults exposure. Finally, taking the possible exposure of children contacting with lip products, the health risk assessment of children blood Pb was carried out. The results showed that the concentration of Pb in lip products ranged from 0 to 0.5237 mg/kg, which was far lower than the limit set by various countries. The probabilistic non-carcinogenic risks and carcinogenic risks were 4.93 ×10−7~2.82 ×10−3 and 1.68 ×10−12~9.59 ×10−9, respectively, which were in an acceptable level. The results of blood Pb assessment suggested that the Pb content of lip cosmetics had no obvious influence on blood Pb concentration of children, and background Pb exposure is the main factor affecting children's blood Pb level (BLL). Overall, the samples of lip products are selected by Python crawler in this study, which are more objective and representative. This study focuses on deeper study of Pb, especially for the health risk assessment of blood Pb in children exposed to lip products. These results perhaps could provide useful information for the safety cosmetics usage for people in China and even the global world.